Persaingan Industri dan Subtitusi Industri Terhadap Perkembangan Industri - Dyah Febiyani Nuralifia; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The industrialization policies taken by the governments of developing countries are carried out for several reasons. First, developing countries usually always experience difficulties in their balance of payments, so import substitution is intended to reduce or save foreign exchange. Moreover, foreign exchange for developing countries is often a scarce factor, so choices must be made regarding its use. Third, it is related to the spirit of nationalism in a country, so that it adopts an industrialization policy with the aim of achieving independence in the economic sector. The industrialization strategy is based on efforts to substitute imports of goods and services, which essentially focuses on the large dependence of developing countries, especially on the production of goods and services in developed countries. As a result, many developing countries have chosen an export-oriented strategy for their industrial development. Nevertheless, import substitution industries still play an important role in industrial development for developing countries, especially in several manufacturing sectors. Several countries choose to use an import substitution industrial strategy in the early stages of industrialization, including Indonesia. The import substitution industry is still able to make an important contribution to economic growth in developing countries.